2008
DOI: 10.1021/ol801290g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Sensing of IP3 with a Trifurcate Zn(II)-Containing Chemosensing Ensemble System

Abstract: A trifurcate receptor containing Zn(II)-dipicolylamine ligands is developed for the fluorescent sensing of IP 3, myo-inositol 1,4,5-tris(phosphate), through an indicator displacement approach. The chemosensing ensemble containing the Zn(II) complex and eosin Y as indicator shows the maximum fluorescence restoration for IP 3 among various other anions including phosphate derivatives in water buffered at pH = 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…A similar strategy to increasing binding affinity has been employed by Gunning and co-workers who have developed a systematic synthetic route to orthogonally functionalized bis[Zn(II)-DPA] receptors based on the m-xylylene scaffold 53, providing a library of asymmetrically functionalized bis[Zn(II)-DPA] complexes 70-77. 87 Anion binding studies by isothermal titration calorimetry in 50 mM HEPES buffer (pH 7.4) at 25 1C showed that of those receptors examined (53,(70)(71)(72)(73)(74), receptor 71 has the highest affinity for NaH 2 PO 4 (K ass = 1.5 Â 10 6 M À1 ), which represents B10-fold enhancement over the unsubstituted receptor 53. However, the introduction of hydrogen bonding groups did not increase binding affinity in all cases, with 73 and 74 having similar and slightly lower affinity, respectively, for NaH 2 PO 4 to that exhibited by the parent 53.…”
Section: àmentioning
confidence: 97%
See 2 more Smart Citations
“…A similar strategy to increasing binding affinity has been employed by Gunning and co-workers who have developed a systematic synthetic route to orthogonally functionalized bis[Zn(II)-DPA] receptors based on the m-xylylene scaffold 53, providing a library of asymmetrically functionalized bis[Zn(II)-DPA] complexes 70-77. 87 Anion binding studies by isothermal titration calorimetry in 50 mM HEPES buffer (pH 7.4) at 25 1C showed that of those receptors examined (53,(70)(71)(72)(73)(74), receptor 71 has the highest affinity for NaH 2 PO 4 (K ass = 1.5 Â 10 6 M À1 ), which represents B10-fold enhancement over the unsubstituted receptor 53. However, the introduction of hydrogen bonding groups did not increase binding affinity in all cases, with 73 and 74 having similar and slightly lower affinity, respectively, for NaH 2 PO 4 to that exhibited by the parent 53.…”
Section: àmentioning
confidence: 97%
“…14). 74,75 In HEPES buffer solution (10 mM, pH 7.0), receptor 60 binds to eosin Y with a 1 : 2 stoichiometry as determined by fluorescence and UV-vis titrations. 74 The association constants were found to be K 1 = 1.2 Â 10 6 M À1 and K 2 = 8.2 Â 10 4 M À1 by UV-vis titrations.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) have been scrutinized for understanding the activation of C-H bonds [25][26][27] and obtaining stimuli-responsive switches/ sensors. 19,28,29 In TPA coordination systems, the propeller-like chirality was controlled with an alkyl substituent: the alkyl group would, as a relay auxiliary, 30 promote the formation of predominantly one twisted diastereomer (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Anslyn 9 , 10 , Ahn 11 , Yoon 12 , 13 , Aoki 14 , 15 and Best 16 have previously reported receptors for inositol phosphates such as IP 3 based on scaffolds substituted with phosphate-recognition moieties such as guanidinium, alkyl ammonium or imidazolium groups as well as zinc(II) complexes. While these receptors have shown high affinity and, in some cases, good selectivity for specific IPs (mainly IP 3 ), their binding to PIPs (i.e.…”
Section: Introductionmentioning
confidence: 99%